2009
DOI: 10.1007/s11703-009-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Influences of leaf litter replacement on soil biochemical characteristics of main planted forests in Qinling Mountains of China

Abstract: Long-term continuous growth of the same tree species in planted pure forest will lead to soil polarization and degradation. Mixed forestation or litter replacement between different needle-and broad-leaved forests are effective measures, except fertilization, to control soil polarization according to the mutual compensation principle of different tree species. Through a two-year leaf litter replacement experiment in 4 typical planted pure forests of Larix kaempferi, Pinus tabulaeformis, Catalpa fargesii and Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Catchment land use (agriculture and urban areas) is also a major influence on lake algal biomass (Allan, 2004; Carpenter et al, 1998; Jones et al, 2020; Soranno et al, 2015) and serves as a proxy for lakes’ altered nutrient concentrations (Foley et al, 2005; Vanni et al, 2011). Constructed forest areas may amplify eutrophication by increasing soil nutrient contents (Liu et al, 2008). However, high proportions of upstream forest and grassland areas prevent direct inflow of nutrients into freshwater lakes and can sustain water quality where anthropogenic activities are minor (Wiley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Catchment land use (agriculture and urban areas) is also a major influence on lake algal biomass (Allan, 2004; Carpenter et al, 1998; Jones et al, 2020; Soranno et al, 2015) and serves as a proxy for lakes’ altered nutrient concentrations (Foley et al, 2005; Vanni et al, 2011). Constructed forest areas may amplify eutrophication by increasing soil nutrient contents (Liu et al, 2008). However, high proportions of upstream forest and grassland areas prevent direct inflow of nutrients into freshwater lakes and can sustain water quality where anthropogenic activities are minor (Wiley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Shandong Agricultural University (in Chinese with English abstract). Fu, G., Liu, Z., & Cui, F. (2008) Zhang, T., & Wu, W. (2002). Phosphorus sorption and release of paddy soils: effect of alternation of oxidized and reduced conditions.…”
Section: Auth O R Co Ntr I B Uti O N Smentioning
confidence: 99%
“…Zhang et al (2018) showed that the litter decomposition rate is an important major factor affecting soil nutrient dynamics following afforestation [ 10 ]. Some studies have further shown that litter quality and quantity influenced both soil microbial biomass and enzyme activity [ 11 , 12 , 13 , 14 ], Hu et al (2005) found that the responses of soil microbiological properties to litter decomposition were much more sensitive than those of soil chemical properties [ 15 ]. Although these studies have been conducted in much detail, studies addressing the effects of different plant species on soil microbiological properties are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%